(untitled) (Indian Journal of Public Health Research & Development, 2021)
Diabetes Mellitus (DM) is one of the non-communicable diseases that has the most prevalence of diseases globally. This study aimed to determine the characteristics of patients type 2 diabetes mellitus (T2DM) in regional hospital, East Jakarta. The study’s characteristics were age, sex, education, occupation, Body Mass Index (BMI), history of diabetes mellitus, history of hypertension, and blood pressure. The study design uses descriptive studies. The study population was all people with diabetes mellitus in regional hospital, East Jakarta. This study sample was people with type 2 diabetes mellitus in January to March 2019 in the regional hospital, 170 patients. The sampling technique is by using non-random sampling. The results showed that people with type 2 diabetes mellitus aged over 45 years 86%, male sex 52%, higher education 78.82%, not working 55%, normal BMI 48%, had a history of DM 54%, have a history of hypertension 57%, and normal blood pressure 65%. The study population’s conclusions were all people with diabetes mellitus in the regional hospital, East Jakarta, aged over 45 years, male sex, higher education, not working, normal BMI, had a history of DM, have a history of hypertension, and normal blood pressure.